Electric Current as a Driving Force for Interphase Growth in Spark Plasma Sintered Dielectric Composites. Issue 2 (6th January 2016) - Albino, Marjorie; Chung, U‐Chan; Kassas, Ahmad; Lesseur, Julien; Bernard, Dominique; Elissalde, Catherine; Maglione, Mario
Abstract : All‐oxide composites are increasingly investigated in the field of microelectronics and telecommunications because of their multifunctionalities. Advanced control of interfaces is required to fully tune the macroscopic properties of the composites. Processing ferroelectric Ba0.65 Sr0.35 TiO3 (BST65/35)‐TiO2 composites by Spark Plasma Sintering (SPS), we show that the SPS electric current promotes an interphase growth whose thickness depends on the BST/TiO2 stacking and on the current direction. In all cases, the interface is composed of Ba1.14(2) Ti8 O16‐δ a highly defective, but stable phase which can be used to tune the overall dielectric properties of the composites.